Structural, Electric and Thermoelectric Studies of CaFeO3 System - Khan, M. N.; Zafar, N. (The Nucleus, 2015)
Polycrystalline CaFeO3 samples were synthesized through solid state route at 1000 oC. The sintered samples were analyzed by XRD for crystal structure analysis. Electrical resistivity and seebeck coefficient were also measured for transport properties. The Rietveld analysis performed on the XRD data revealed that the sample is single phase with orthorhombic crystal symmetry. The space group was found to be pcmn. Power factor has been obtained from Seebeck Coefficient and electrical resistivity data. Electrical resistivity showed that conduction in the sample occurred through variable range hopping of the electrons. The negative Sign of Seebeck coefficient revealed that majority charge carriers in these samples are electrons. The properties determined make this material a potential candidate for electric and thermoelectric device applications.